N-acetylcysteine Treatment Protects Intestinal Mitochondria in a Surgical Stress Model - Reza Heidari; Khadijeh Mousavi; Shayesteh Amin; Mohammad Mehdi Ommati; Hossein Niknahad (Shiraz University of Medical Sciences, 2020)
Surgery-associated small intestine damage is a clinical complication. It has been found that opening the abdominal cavity during surgery and manipulation of organs, including the intestine, could lead to intestinal barrier disintegrity and the entrance of pathogens to the systemic circulation. Hence, finding agents to protect the intestine during surgical manipulation could have clinical value. Oxidative stress and enterocytes mitochondrial dysfunction and energy (ATP) crisis are the proposed mechanisms for surgery-induced intestinal damage. N-acetylcysteine (NAC) is a thiol reducing agent and radical scavenging molecule which is widely investigated for its pharmacological properties. The current study was designed to evaluate the effects of NAC treatment on the surgery-induced mitochondrial dysfunction in an animal model. Rats were treated with NAC (500 and 1000 mg/kg, oral) and underwent surgical stress. Afterward, the small intestine mitochondria were isolated and assessed. The effects of surgical stress on small intestine mitochondrial was revealed as a significant decrease in mitochondrial dehydrogenase activity, mitochondrial depolarization, decreased mitochondrial ATP levels, and mitochondrial permeabilization. Moreover, the level of alkaline phosphatase secretion from the intestinal brush border was increased. It was found that NAC treatment significantly alleviated ALP levels, and improved mitochondrial indices when this drug was pre-treated (1 week) to rats. Collectively, it could be concluded that NAC treatment might be a therapeutic approach against surgery-induced intestinal damage. The effects of NAC on mitochondrial function seem to has a pivotal role in its protective mechanism of action.